Characterization and quality of care indicators in patients with acute myocardial infarction without ST segment elevation. (14th October 2021) - Dias Claudio, F; Rocha, R; Carrington, M; Pais, J; Guerreiro, R; Hyde-Congo, K; Neves, D; Santos, A R; Picarra, B; ,
Abstract: Introduction: The definition of the quality of care in healthcare services is paramount to implement the resources necessary to grant the best quality of care according to the current guidelines. Recently, the European Society of Cardiology's guidelines for the management of acute coronary syndromes without ST segment elevation (NSTEMI) were published, and defined the quality indicators to be evaluated in such patients. Purpose: To characterize the level of care given to the population of patients with NSTEMI included in the a national registry since 2011, according to the new guidelines directives. Population and methods: We evaluated 12193 patients with NSTEMI. For each year the following variables were analyzed: age, gender, cardiovascular and non-cardiovascular comorbidities, clinical presentation (rhythm, blood pressure, Killip-Kimball Class), left ventricular ejection fraction (LVEF), treatment during admission and discharge, and time to invasive coronary angiography (ICA). Besides this, a comparing between years was made to analyze differences according to the quality indicators established in the guidelines. Results: In 2019, 83.9% of patient with LVEF <40% were treated with IECA/ARA II and 80.6% were prescribed a betablocker at discharge. No statistically significant differences were found across the year with respect to IECA/ARA II at discharge (p=0.495), and beta-blocker at discharge (p=0.812). In terms of P2Y12 inhibitors during the hospital admission, there was a statistically significant increase in its use when comparing 2019 to 2014, 2015, 2016 and 2017 (p=0.019 for 2014 and p<0, 001 the following years), with prescription in 90.4% of the patients in 2019. At discharge 88.3% of the patients were prescribed a P2Y12 inhibitor in 2019 and there was also a statistically significant increase in its prescription when compared to the previous years (from 2011 to 2017 with a p<0.001). When it comes to the prescription of statins at discharge there was a statistically significant difference between groups, driven mostly by an increase compared to the year 2012 (95.6% vs 90.8%, p=0.005). Only 16% of patients were subjected to ICA within 24h of admission during the year 2019. No statistically significant difference was found between other years (p>0.100 when comparing between years). Discussion: The most striking feature that can be improved is the amount of patients subject to ICA within the first 24h after diagnosis. When it comes to the P2Y12 inhibitors it is also clear that there has been an increase in its prescription during the admission and at discharge. To sum up, it is clear that there is still some margin to improve care, of at least 10–20% in most parameters. This data portrays a picture of the measures and steps to take in order to provide the adequate care according to the latest guidelines. Funding Acknowledgement: Type of funding sources: None.